Relationship between the left ventricular size and the amount of trabeculations. (1st December 2017) - Paun, Bruno; Bijnens, Bart; Butakoff, Constantine
Abstract: Contemporary imaging modalities offer noninvasive quantification of myocardial deformation; however, they make gross assumptions about internal structure of the cardiac walls. Our aim is to study the possible impact of the trabeculations on the stroke volume, strain, and capacity of differently sized ventricles. The cardiac left ventricle is represented by an ellipsoid and the trabeculations by a tissue occupying a fixed volume. The ventricular contraction is modeled by scaling the ellipsoid whereupon the measurements of longitudinal strain, end‐diastolic, end‐systolic, and stroke volumes are derived and compared. When the trabeculated and nontrabeculated ventricles, having the same geometry and deformation pattern, contain the same amount of blood and contract with the same strain, we observed an increased stroke volume in our model of the trabeculated ventricle. When these ventricles contain and eject the same amount of blood, we observed a reduced strain in the trabeculated case. We identified that a trade‐off between the strain and the amount of trabeculations could be reached with a 0.35‐ to 0.41‐cm dense trabeculated layer, without blood filled recesses (for a ventricle with end‐diastolic volume of about 150 mL). A trabeculated ventricle can work at lower strains compared to a nontrabeculated ventricle to produce the same stroke volume, which could be a possible explanation why athletes and pregnant women develop reversible signs of left ventricular noncompaction, since the trabeculations could help generating extra cardiac output. This knowledge might help to assess heart failure patients with dilated cardiomyopathies who often show signs of noncompaction. Abstract : Using a geometrical model of the left ventricle, we show that a trabeculated ventricle can work at lower strains compared to a nontrabeculated one to produce the same stroke volume; the trabeculations help increasing stroke volume with less strain; it is possible to find the amount of trabeculations, where stroke volume is optimized while left ventricular size remains within physiological ranges; the trabeculations are necessary for a more efficient cardiac function, even a small amount of them can be beneficial.